The collapse and recovery of the capital share in East Germany after 1989 - Simona E. Cociuba (The University of Western Ontario, Department of Economics, 2018)
After the 1990 unification, East Germany's capital income share plunged to 15.2 percent in 1991, then increased to 37.4 percent by 2015. To account for these large changes in the capital share, I model an economy that gains access to a higher productivity technology embodied in new plants. As existing low productivity plants decrease production, the capital share varies due to the non-convex production technology: plants require a minimum amount of labor to produce output. Two policies - transfers and government-mandated wage increases - have opposite effects on output growth, but contribute to lowering the capital share early in the transition.
Keywords: E20; E25; O11; 330; technological change; capital share; labor share; transfers; union markups